KONSEP KETUHANAN DALAM FILSAFAT POSTMODERNISME PERSPEKTIF KEREN AMSTRONG - Marsono (Sanjiwani: Jurnal Filsafat, 2018)
Postmodernism is a critical reflection on the paradigms of modernism an the era of the rise of religious spirituality. This study discusses about the concept of God in philosophy of postmodernism. The existence of God and religion has always incited discourses throughout the history of mankind. The unresolved debates spawning a variety of viewa are distinctive one to another and even contradictory. The discussion uses philosophy of divinity in perspective of Karen Amstrong in order to obtain a through and fundamental understanding of the nature of faith in perspective of Karen Amstrong, author of best selling books, “History of God” and “The Future of God”.